Prevalence of Trichomonas vaginalis Infection in Women Screened for Precursor Lesions of Cervical Cancer in a Brazilian Population - Santos, Marina de Paula Salomé dos [UNESP]; Ramos, Bruna Ribeiro de Andrade [UNESP]; Oliveira, Maria Luiza Cotrim Sartor de [UNESP]; Tristão, Andréa da Rocha [UNESP]; Silva, Márcia Guimarães da [UNESP] (MDPI, 2024)
Trichomonas vaginalis infection is one of the most prevalent curable STIs. Although treatments are available, T. vaginalis infections pose a significant challenge, especially in resource-limited regions, as the prevalence of this STI is often unknown. We aimed to determine the prevalence of Trichomonas vaginalis infection in women screened for cervical cancer precursor lesions in Botucatu in São Paulo, Brazil. We conducted a descriptive and retrospective study that included 23,735 women who attended the cervical cancer screening program at health units in 2019 and 2022. Clinical and sociodemographic data were collected from the cancer information system (SISCAN) and test requisition forms. Descriptive analysis was conducted, and comparisons were performed using the X2 Test and Student’s t-test (SigmaPlot version 13.0). The prevalence of T. vaginalis infection was 0.84% in 2019 and 0.57% in 2022. The mean age of patients with trichomoniasis was 42 (±11.2) years; 75% self-reported as white, 43% were married or in a stable relationship, and 40% had not completed primary education. Regarding the vaginal microbiota, only 15.3% of the cytology exams with infection by T. vaginalis showed a predominance of lactobacilli species, while inflammation was present in 82% of the smears. Cytological analysis revealed precursor lesions of cervical cancer in 0.05% of patients with trichomoniasis, including ASC, LSIL, and HSIL. The study showed a low prevalence of infection with T. vaginalis in low-risk women screened for precursor lesions of cervical cancer in Botucatu in São Paulo, Brazil.
Keywords: cervical cytology; pap smear; sexually transmitted infection; Trichomonas vaginalis; trichomoniasis